PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT KONSUMEN MOBIL MITSUBISHI TIPE PAJERO (Kasus Dealer Pekan Perkasa Berlian Motor Pekanbaru ) - Rasyadi, Ilham; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine how the influence of promotion (inform, introduce, persuading, and reminding) and Quality of Service (Tangibles, Ephaty, Reliaility, Responsiveness and Assurance) against the interests of consumers (Attention, interest, Desire, and Action) Dealer Pekan Perkasa Berlian Motor Pekanbaru.The population in this study is that consumers who buy cars Mitsubishi Pajero type Dealer Pekan Perkasa Berlian Motor Pekanbaru. With 100 samples, sampling using the formula slovin. The data collection of primary data research, with questionnaires as an instrument of research and secondary data from company archives, data analysis used is by using multiple linear regression, determination test, t test and f SPSS.From the results of data analysis include validity, reliability, and multiple linear regression, t test research results showing the calculation of the t (4.306)> t table (1.985) and Sig. (0.000) <0,05.Artinya variable Promotion significantly influence Consumer interest.And the results showed the calculation of the t (7.098)> t table (1.985) and Sig. (0.000) <0.05 .. That variable significant effect on the Quality of Service and Consumer Interests based test concluded that the simultaneous sale and service together significant effect on consumer interest with the influence of 81.78% in Pekan Perkasa Berlian Motor Dealer Pekanbaru.Keywords: Promotion, Quality of Service, Consumer Interests